Update on SARS research and other possibly zoonotic coronaviruses() - Anderson, Larry J. (Int J Antimicrob Agents, 2010)
The global outbreak of severe acute respiratory syndrome (SARS) in 2003 led to an intense and effective global response that stopped the spread of the disease by July 2003. There was also an intensive and very productive research effort to identify the aetiological agent, characterise the clinical and epidemiological features of the disease, understand the pathogenesis of the disease and the molecular biology of the virus, and design antiviral drugs and vaccines to treat and prevent the disease. In parallel with the SARS research effort there have been continuous improvements in our ability to detect and characterise other novel viruses. The SARS outbreak illustrates the importance of such detection tools in the response to public health threats. Studies since the SARS outbreak suggest that many novel viruses exist in animals and some, but probably not many, will present a risk to humans.